Photonic Band Gap Material Topological Design at Specified Target Frequency (Adv. Theory Simul. 10/2021). Issue 10 (4th October 2021) - Zhang, Xiaopeng; Luo, Yangjun; Yan, Yi; Liu, Pai; Kang, Zhan
Abstract : Photonic Crystals Optimization at Specified Target Frequency To achieve any specified band gap photonic crystal (PhC) structure around the target frequency, a new band gap measuring index and topological design strategy are reported in article number 2100125 by Xiaopeng Zhang, Yangjun Luo, Yi Yan, and co‐workers. The cell topology is represented with only 50 design variables through the material‐field series‐expansion, and the multi‐peak optimization problem is solved by the sequential Kriging‐based algorithm. The cover shows an ultra‐wide band gap PhC device.